The Factors Affecting Teachers’ Readiness In Developing Science Concept Assessment Through Inquiry-Based Learning Process In Elementary Schools - Budiastra, A.A. Ketut; Erlina, Nia; Wicaksono, Iwan (Advances in Social Sciences Research Journal, 2019)
Teachers need to develop their professionalism in teaching to achieve 21st century learning competencies. The role of the teacher is not only to provide information but also to assess the learning process and outcomes comprehensively and in an integrated manner. This study aimed to describe the factors that support the readiness of teachers to carry out assessments in inquiry-based science in elementary schools. Respondents in this study were 87 elementary school teachers who were 87 students spread across four regions of the UT Regional Office namely Pangkalpinang, Jakarta, Denpasar, and Kupang. These four regions of the UT Regional Office were chosen as a representation of the regions of West, Central and East Indonesia. From this sample, teachers were examined to see their readiness to compose a lesson plan and carry out an inquiry assessment. Next, teachers filled in the response sheet to find out their readiness to carry out an inquiry assessment in science learning in elementary schools. Teaching inquiry-based science required teachers to spend more time preparing lesson plans to prepare tools and learning materials. Factors which supported the readiness of teachers to measure the inquiry-based science learning process in elementary schools, including their sufficient capacity to develop lesson plans which were oriented to the inquiry process, peer support and teachers’ working group. Some efforts were done to overcome obstacles namely developing the ability to assess the mastery of science concepts through inquiry-based learning processes in elementary schools, utilizing teachers’ working group (TWG) and the support of school principals/assessors to make relevant assessment tools.